Dari Logika Dominasi Menuju Logika Advokasi: Kekerasan Simbolik dalam Wacana Kewargaan di Indonesia - Lelono, Martinus (Reformed Center for Religion and Society, 2024)
In the study of citizenship in Indonesia, the term majority-minority is well recognized. This paper aims to challenge the power dynamics behind the majority-minority discourse in Indonesia. Discussions about minorities, which were initially intended as a means of advocacy, have transformed into a tool of domination. In the context of Identity Politics in the latter half of the 20th century, minorities were associated with the defense of Black people in the United States, as well as gay and lesbian communities, and Native American groups. In Indonesia, however, the discourse on majority and minority has shifted tonumerical considerations. This discourse is evident in conversations about citizenship in Indonesia, particularly regarding religious backgrounds, leading to the terms majority religion and minority religion. Using the Netnography method, this research explores various ways of interpreting the term minority within Indonesian society. This study employs Pierre Bourdieu's theory of Symbolic Violence as its analytical framework. From this perspective, it is revealed that the prevailing discourse is not about majority-minority but rather the process of minoritization. This paper proposes a counter-current logic. The prevailing logic of domination associated with the term minority is encouraged to revert to the advocacy logic that originally inspired it.